Internal Quality Assurance Model at Samarinda Midwifery Academy - Evy Nurachma; Lambang Subagiyo; Johansyah (Journal La Edusci, 2020)
The objectives to be achieved through this research are describe the Quality Assurance Model, Formulate the Quality Assurance Model, Describe the inhibiting factors and solution of the Quality assurance system at the Husada Flower Midwifery Academy, the Mahakam Pearl Midwifery Academy and the East Kalimantan Health Polytechnic. This study uses a qualitative approach to the type. Data collection techniques are carried out through in-depth interviews, participant observation and documentation. Establish procedures for preparation of implementation and required resources. Prepare human resources through the process of training, workshops and discussions. Samarinda Mahakam Pearl Midwifery Academy Samarinda. Conducted based on: Academic documents: quality standards that have been set. Quality document: as an instrument to achieve predetermined standards. Poltekkes Kemenkes East Kalimantan, The implementation of improving the quality assurance system is guided by: quality assurance principles oriented to inputs, processes and outputs. Formulation of Quality Assurance, preparation of quality improvement strategy plans is carried out systematically and structured in each midwifery academy which is oriented towards improving the quality of inputs, processes and outputs, with different strategies. Inhibiting factors and quality assurance system solutions implemented by carrying out: self-evaluation, internal academic quality audits, solutions carried out to determine the achievement of quality standards that have been set and evaluation findings used as material to improve the quality assurance improvement, which is planned, implemented and evaluated carried out implementation control and improvement in accordance with midwifery vocational education standards properly.